2019
DOI: 10.1155/2019/4632946
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Remote Self-Management of Chronic Low Back Pain: A Preliminary Study

Abstract: Objective. To assess the additional effect of self-management on physiotherapy via the use of APPS on management of chronic low back pain. Method. A single-blinded randomized control trial was conducted. 8 participants (male: 4; female: 4) were recruited from the Rehabilitation Clinic of The Hong Kong Polytechnic University. Participants in the treatment group received self-management plus physiotherapy and the control group received physiotherapy only. Assessment was carried out pretreatment, midterm (week 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 47 publications
0
67
1
Order By: Relevance
“…The subjects investigated in this study were recruited from the Rehabilitation Clinic of The Hong Kong Polytechnic University and were treated with respectively physiotherapy (Group 1) or physiotherapy + smartphone-based remote selfmanagement (Group 2). The mean PSEQ scores at baseline in [54] (Group 1: 34.3 ± 8.0; Group 2: 38.6 ± 8.5; mean ± SD) were lower than the mean PSEQ score of the subjects investigated in the present study (49.0 ± 10.6). However, there are a number of substantial shortcomings in [54] which renders this study insufficient for contributing to evaluating the mean PSEQ score of subjects with cnsLBP who seek treatment at a department of pain medicine in China: (i) the number of subjects investigated in [54] was very small (Group 1: n=3; Group 2: n=5) and, thus, the total number of subjects investigated in [54] (n=8) was less than 20% of the number of subjects in each group investigated in the present study; and (ii) the only inclusion criteria reported in [54] were nonspecific low back pain due to musculoskeletal origins, access to a mobile phone and the ability to perform a brief exercise during regular working hours; and the only exclusion criterion reported in [54] was history of receiving major surgery.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The subjects investigated in this study were recruited from the Rehabilitation Clinic of The Hong Kong Polytechnic University and were treated with respectively physiotherapy (Group 1) or physiotherapy + smartphone-based remote selfmanagement (Group 2). The mean PSEQ scores at baseline in [54] (Group 1: 34.3 ± 8.0; Group 2: 38.6 ± 8.5; mean ± SD) were lower than the mean PSEQ score of the subjects investigated in the present study (49.0 ± 10.6). However, there are a number of substantial shortcomings in [54] which renders this study insufficient for contributing to evaluating the mean PSEQ score of subjects with cnsLBP who seek treatment at a department of pain medicine in China: (i) the number of subjects investigated in [54] was very small (Group 1: n=3; Group 2: n=5) and, thus, the total number of subjects investigated in [54] (n=8) was less than 20% of the number of subjects in each group investigated in the present study; and (ii) the only inclusion criteria reported in [54] were nonspecific low back pain due to musculoskeletal origins, access to a mobile phone and the ability to perform a brief exercise during regular working hours; and the only exclusion criterion reported in [54] was history of receiving major surgery.…”
Section: Discussioncontrasting
confidence: 74%
“…Until now the PSEQ score has not been used in any study listed in PubMed on treatment of cnsLBP performed at a department of pain medicine in China. One study on this topic authored by Chinese authors has been listed in PubMed so far [54]. The subjects investigated in this study were recruited from the Rehabilitation Clinic of The Hong Kong Polytechnic University and were treated with respectively physiotherapy (Group 1) or physiotherapy + smartphone-based remote self-management (Group 2).…”
Section: Discussionmentioning
confidence: 99%
“…After title and abstract screening, 83 articles were included in the full-text screening; 22 unique studies with a total of 4679 patients met the eligibility criteria (1515 in non-RCT designs, 3164 in RCT designs) ( Figure 1). For the meta-analysis, 12 of these studies were considered as RCTs [36][37][38][39][40][41][42][43][44][45][46][47], while 10 were observational or studies of similar design, which compared baseline measures to post-intervention measures of the same individuals [48][49][50][51][52][53][54][55][56][57]. Studies varied in sample sizes, sex distributions, populations, assessment instruments, and study quality.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were aimed at individuals with general chronic pain [40,41,51,52,56,57], nine studies at individuals with chronic lower back pain (LBP) [36,37,39,44,46,47,49,53,54], three studies at individuals with arthritis (e.g., osteoarthritis and rheumatoid arthritis) [43,45,55], and one study each at individuals with menstrual pain [48], frozen shoulder pain [38], chronic neck pain [42], and migraine [50]. Fifteen of the studies recruited patients during clinic visits or through their general practitioners (GP) [36][37][38][40][41][42][43][46][47][48]51,52,[55][56][57] or research institutions, and seven recruited participants from the community via the internet or flyers [39,44,45,49,50,53]. All studies included both sexes, except two which included only women [41,55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation